Diet and physical activity as treatment for obesity, diabetes, and cardiovascular disease - Velázquez López, Lubia; Escobedo de la Peña, Jorge (Horizonte Sanitario, 2026)
Obesity is associated with an increased risk of developing diabetes, cardiovascular disease (CVD), and certain types of cancer, which are the leading causes of morbidity and mortality in Mexico. There is sufficient evidence of the global obesity pandemic. In turn, diabetes and cardiovascular disease have been reported as the leading causes of mortality in Mexico. These conditions have a significant impact on healthcare institutions and those who suffer from them. The treatment of these conditions requires a comprehensive approach, in which the adoption of a healthy diet and physical activity are fundamental to their prevention and to reducing the risk of complications associated with these diseases. Adopting a healthy lifestyle with a diet that includes more fiber, such as fruits and vegetables, legumes, and oilseeds, as well as reducing red meat, sugars, and processed foods. The importance of regular physical activity as part of one’s lifestyle and reducing sedentary habits in daily life is highlighted. Adherence to a healthy diet in combination with regular physical activity are important components to be implemented by the health team to reduce the incidence of these diseases, which have a high burden of morbidity and mortality in Mexico, as well as to reduce the risk of complications associated with these diseases. Keywords: Obesity; Type 2 diabetes mellitus; Heart disease; Diet; Physical exercise.